Protótipo de um sistema antifurto de motocicleta - Batista, Rodrigo de Moraes (Brasil, 2023)
Many people have their motorcycles stolen every day in Brazil, according to a survey carried out by HelloSafe Brasil, thus causing various inconveniences and losses. The objective of this work is the development of a security mechanism to hinder motorcycle thefts, through a method of automatic identification of the owner through radio signals. A quantitative survey was carried out, that is, an opinion survey, where some people were interviewed, in order to verify the acceptance and viability of the development of a system against theft of motorcycles. At the end of this work, it was verified by the research carried out, that the proposed product could help in the reduction of motorcycle thefts. On the other hand, the concepts learned during graduation enabled the development of a functional prototype.